PENINGKATAN KAPASITAS UMKM MELALUI PELATIHAN MANAJEMEN KEUANGAN DAN PEMASARAN DIGITAL PRODUK UMKM KERUPUK TIKE DI DESA DOMAS KECAMATAN PONTANG - Saputra, Saripudin; Mahendra, Yoga; Permata, Nuniek; Alamsyah, Alamsyah; Diantoro, Eman (Batara Wisnu : Indonesian Journal of Community Services, 2024)
This study aims to enhance the capacity of micro, small, and medium enterprises (MSMEs) producing kerupuk tike in Domas Village, Pontang District, through training in financial management and digital marketing. Based on the background, MSMEs in the village face challenges in effective financial management and marketing. The method used involves interactive training and mentoring, which are expected to improve the participants’ knowledge and skills. The research results show a significant increase in financial management understanding, with participants’ knowledge rising from 30-40% to 70-80% after the training. Additionally, the use of social media and e-commerce platforms successfully increased average monthly sales from IDR 1,500,000 to IDR 3,500,000. Participants’ motivation to develop their businesses also improved, as indicated by an increase in monthly transactions from 15 to 30. Despite challenges in consistently applying the learned skills, the need for long-term mentoring is crucial to ensure the sustainability of the taught methods. In conclusion, this community service activity positively impacts the MSMEs in Domas Village, with capacity improvements that can support their future business success